Analisis Tingkat Literasi Keuangan Mahasiswa STIE Ciputra Makassar dengan Jalur Sukses StartUp Business - Cindy Yoel Tanesia; Yuyun Karystin Meilisa Suade; Lakshmi Jaya Ningsih; Shakira Ayesha; Andrean Kevin (Jurnal Mirai Management, 2022)
This study aims to analyze the financial literacy level of first year students in STIE Ciputra, Makassar and the influencing factors behind it. The survey was distributed to 100 students but only 82 could be used. The data collected were processed through descriptive statistics analysis and ANOVA test. It is found that the financial literacy level of the students is 63.26% which is in medium level. It is also found that there were 2 factors that significantly affect the financial literacy level such as living situation and ethnicity. The lowest literacy level of 53.63% was debt literacy and the highest literacy level of 77.25% was money management. This indicates that there’s a need to enhance and improve the level of debt literacy. Keywords: literasi keuangan, mahasiswa, ethnicity